A possible case of etoricoxib induced fixed drug eruption - ., Apoorva; K., Girish; Manjunath, Namrata C. (International Journal of Basic & Clinical Pharmacology, 2019)
Fixed drug eruption (FDE) is a most commonly with adverse drug reaction seen with use of Non-steroidalanti-inflammatory drugs (NSAIDs) in particular nimesulide followed by antibiotics and anticonvulsants. Etoricoxib is a selective cyclo-oxygenase isoenzyme-2 inhibitor which is superior to conventional NSAIDs and causes less side effects. Authors present a case of fixed drug eruption due to etoricoxib in a male patient. A 50-year-old patient presented to Outpatient Department (OPD) of Dermatology of a Tertiary Care Hospital with complains of skin rashes over lips, oral cavity, trunk, both the upper and lower limbs, palm, soles, scrotum and glans penis since a week. The detailed history of the patient revealed the use of etoricoxib a week back, prescribed for low back pain. It was suspected that the cutaneous drug reaction was due to the use of etoricoxib. The suspected drug etoricoxib was stopped, patient was admitted and managed symptomatically. The above reaction was assessed to be “possible” as per WHO-UMC and Naranjo causality scale, “moderate” on Hartwig’s scale and “Probably preventable” according to Schumock and Thornton criteria. This case reporting was done to sensitize the prescribers regarding rare side effects of the above drug and the need to confirm past history of drug reaction before prescription.